Optimizing an Infusion Method of Producing Cosmos Caudatus Encapsulated In Exosomes as A Nanocarrier for Drug Delivery - Ahmed, Alhakam; Amir, Wan; Shahidan, Wan Nazatul Shima (Journal of Health Science and Medical Research, 2025)
Objective: This study aimed to propose different encapsulation methods of a medicinal plant extract Cosmos Caudatus (CC), into HSC-2-derived exosomes. Material and Methods: Encapsulation of HSC-2-derived exosomes was achieved via internal and external infusion. The internal infusion was achieved by treating HSC-2 cells with CC extract and isolating the exosomes from its media (M1_ExoCC). The external infusion was performed by dissolving CC extract with HSC-2 purified plain culture media (M2_ExoCC), direct incubation of isolated exosomes suspended in PBS with CC extract (M3_ExoCC), freeze-thaw incubation of purified HSC-2 media containing CC extract (M4_ExoCC), and freeze-thaw incubation of PBS suspended exosome with CC extract (M5_ExoCC). Results: M1_ExoCC and M2_ExoCC were the most advantageous encapsulation methods in terms of yield, stability and solubility. Conclusion: It was determined that the M1_ExoCC and M2_ExoCC methods yielded the most favorable outcomes across all parameters. The cost-effectiveness and simplicity of these methods make them particularly appealing for scaling up production and translating research findings into clinical practice.